Das Wagnis der Interpretation zwischen Geistesgeschichte und Werkimmanenz: Paul Kluckhohn, Fritz Martini und Heinz Otto Burger - Krumeich, Jens (Scientia poetica, 2023)
Work-immanent interpretation (Werkimmanentes Interpretieren) is a theoretically, methodologically and practically interesting topic with a colorful history. By using Paul Kluckhohn, Fritz Martini, and Heinz Otto Burger as examples, the article traces the lines of development of interpretation in German studies from the Weimar Republic, under Nazism, and to the 1950s. I demonstrate that the didactic and propaedeutic practice of work-immanent interpretation in schools was complementary to the university curriculum from an early stage, balancing, for example, the abstract programs of Geistesgeschichte. The praxeology of German studies has to take these entanglements of school and academic practices into account.
Gesehen am 11.12.2023